2009
DOI: 10.3844/ajassp.2009.219.223
|View full text |Cite
|
Sign up to set email alerts
|

Strength Modeling of High-Strength Concrete with Hybrid Fibre Reinforcement

Abstract: The low tensile strength and limited ductility, the unavoidable deficiency, of concrete can be overcome by the addition of fibres. High strength concrete (HSC) of 60 MPa containing hybrid fibres, combination of steel and polyolefin fibres, at different volume fraction of 0.5, 1.0, 1.5 and 2.0% were compared in terms of compressive, splitting tensile strength and flexural properties with HSC containing no fibres. Test results showed that the fibres when used in hybrid form could result in enhanced flexural toug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Thus, material strain rate effects become critical and must be accounted for in predicting columns performance for short duration loadings such as impact and blast loadings. Many experimental research results were reported in the area of compressive and tensile strength of concrete at different strain rates (Abu-Lebdeh et al, 2010;Ravichandran et al, 2009;Kotsovos, 1983). A selection of the commonly published results is also reported by Saravanan et al, 2010;Bischoff and Perry, 1991;and Malvar and Crawford (1998) as presented in Fig.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, material strain rate effects become critical and must be accounted for in predicting columns performance for short duration loadings such as impact and blast loadings. Many experimental research results were reported in the area of compressive and tensile strength of concrete at different strain rates (Abu-Lebdeh et al, 2010;Ravichandran et al, 2009;Kotsovos, 1983). A selection of the commonly published results is also reported by Saravanan et al, 2010;Bischoff and Perry, 1991;and Malvar and Crawford (1998) as presented in Fig.…”
Section: Introductionmentioning
confidence: 90%
“…6) is given as a function of the dynamic slope, Z d . This softening slope is determined based on the available experimental results (Grote et al, 2001;Ravichandran et al, 2009) and proposed as:…”
Section: Methodsmentioning
confidence: 99%
“…It contributes both pozzolonic and filler effect to the concrete, but more dominantly in filling effects due to its extremely fine particle size. As a result, it drastically increases the water demand of the mixture but it can be overcome by incorporating high range water reducing admixture like superplasticiser (Caldarone, 2009;Neville, 1995;Khatri and Sirivivatnanon, 1995;Ravichandran et al, 2009;Roshan et al, 2010) The finely divided particles reacts aggressively with calcium hydroxide when added to the fresh concrete and forms calcium silicate hydrate, which enhance the resistivity of concrete towards chemical attacks and compressive strength (Caldarone, 2009). The filler effect is resulted by the extremely fine (<1 micrometer) particles.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid fibre or hybridization process of fibres in cementitious composites is achieved by combining different types of fibres, in structural and mechanical properties [5]. Mixtures of hybrid fibre with 1.5% to 2% volume fraction (V f ) with high volume fly ash shows high performance fibre reinforced cementitious composite (HPFRCC) behaviour.…”
Section: Introductionmentioning
confidence: 99%